(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
It is possible to state that there is an international consensus regarding organ trafficking as an illegal activity that constitutes a serious violation of human rights and a threat to individual and public health. Despite this premise, the United Nations has not presented a proposal for a Protocol specific to this phenomenon, leaving only the Palermo Protocol’s restricted mention of trafficking in persons for the purpose of organ extraction, which is an insufficient dimension to properly deal with this crime. On the other hand, the European Council Convention against Trafficking in Human Organs has emerged on the international scene, focusing on the criminalization of illicit extraction and the use of illicitly extracted organs, presenting a broader and more appropriate framework than that which existed until then, with more sophisticated criminal measures, international cooperation in judicial and police matters, as well as preventive and protection measures, taking into account the specific nature of this crime. Certainly, this normative advance will be the international guideline for tackling organ trafficking and the broader adherence of countries could mean that the need for a specific UN protocol for this context is resolved, since the European Council has created, in a more agile way, a necessary but still evolving international instrument for combating this crime. On the other hand, the UN should not shy away from reorganizing its structure to coordinate its agencies in order to help tackle organ trafficking. An important action that could be taken by the prestigious Brazilian judiciary, as well as by Brazil’s notorious and respected community of jurists, is to engage in internal dialog with society and the national legislature so that the country becomes a signatory to this instrument, placing Brazil concretely and directly at the forefront of procedures to combat organ trafficking.